2011
DOI: 10.1186/1472-6882-11-128
|View full text |Cite
|
Sign up to set email alerts
|

Steam sauna and mother roasting in Lao PDR: practices and chemical constituents of essential oils of plant species used in postpartum recovery

Abstract: BackgroundFundamental in traditional postpartum recovery in Lao PDR is the use of hotbeds, mother roasting, steam sauna and steam baths. During these treatments medicinal plants play a crucial role, but little has been published about how the treatments are carried out precisely, which species are used, the medicinal properties of these species, and the medicinal efficacy of their chemical constituents.MethodsSixty-five interviews, in 15 rural villages, with women of 4 different ethnic groups were conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 44 publications
1
22
1
1
Order By: Relevance
“…The flower oil presented a compositional pattern made up of a-pinene (24.1%), b-pinene (14.1%) and t-muurolol (13.0%). It was noted that the quantities of linalool and nerolidol in the leaves and fruits were much lower when compared with a previous investigation (Boer et al 2014). Moreover, some compounds such as a-pinene, d-3-carene, b-phellandrene, zingiberene and t-muurolol present in this study were not identified in the previous study.…”
Section: Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…The flower oil presented a compositional pattern made up of a-pinene (24.1%), b-pinene (14.1%) and t-muurolol (13.0%). It was noted that the quantities of linalool and nerolidol in the leaves and fruits were much lower when compared with a previous investigation (Boer et al 2014). Moreover, some compounds such as a-pinene, d-3-carene, b-phellandrene, zingiberene and t-muurolol present in this study were not identified in the previous study.…”
Section: Resultscontrasting
confidence: 67%
“…However, camphene (15.7%), hexadecanoic acid (10.0%) and octadecanoic acid (8.6%) were the main constituents of the root oil. Camphor (23.2% and 34.1%, respectively) and bornyl acetate (14.5% and 17.0%, respectively) were the main constituents of the leaves and fruits of Amomum vilosum (Boer et al, 2014). Moreover, eucalyptol (23.87%) and limonene (22.77%) were the major components of Amomum tsaoko (Wang et al, 2014).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Mothers may find it uncomfortable and unhygienic not to bathe during the postpartum period, especially in a tropical climate such as Singapore. Hence mothers who observe traditional confinement practices need to negotiate with their caregiver assistants on alternative solutions, which may include the use of medical herbs added to hot water for their daily baths, a practice that has been adopted in countries such as Laos (35) and China (17). This may serve as a potential compromise for mothers to observe traditional confinement practices while maintaining their general personal hygiene at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Der Effekt derartiger Zusätze ist wenig untersucht. Zwar wurden antimikrobielle, schmerzlindernde und antientzündliche Effekte beschrieben [40], welche klinische Relevanz diese jedoch besitzen, sollte Gegenstand weiterer Untersuchungen sein. Weitgehend unbestritten ist die positive Wirkung ätherischer Öle auf die Psyche des Menschen, was im Rahmen einer allgemeinen Prävention durchaus von Bedeutung ist.…”
Section: Verstärkung Der Saunawirkung Durch Zusätze Bei Den Aufgüssen?unclassified